Actividades lúdicas para mejorar la atención e hiperactividad de los estudiantes de 5 a 6 años de la Unidad Educativa Ana Rosa Valdivieso de Landívar en el Cantón - Carrera Bajaña, Maykol Armando (2023)
This research topic deals with recreational activities that will serve to improve the attention and hyperactivity of students aged 5 to 6 years, from the "Ana Rosa Valdivieso de Landívar" educational unit; in the Ventanas canton. The scientific results achieved; In this research carried out, they are: acquisition of scientific, logical knowledge, within the world, international events: Latin American, national, provincial, cantonal and local. The primary motivation for the preparation of this investigative work is to help authorities, teachers and parents to solve the problem of students' lack of attention and hyperactivity, through recreational activities, which will help students improve. their academic performance. To achieve this objective, a rigorous investigation of the contexts that support said result was chosen, which helped to organize the types of existing recreational activities, through which a guide of recreational activities was developed, which will be fundamental for the development of teaching-learning, of learners.